Assessment of genetic diversity among soursop (Annona muricata) populations from Java, Indonesia using RAPD markers - SURATMAN SURATMAN; ARI PITOYO; SRI MULYANI; SURANTO SURANTO (Society for Indonesian Biodiversity, 2015)
Suratman, Ari Pitoyo, Sri Mulyani, Suranto. 2015. Assessment of genetic diversity among soursop (Annona muricata)populations from Java, Indonesia using RAPD markers. Biodiversitas 16: 247-253. The objective of this study was to determine geneticdiversity of the soursop (Annona muricata L.) populations from Java (Indonesia) using RAPD markers. A total of 70 individuals werecollected from 7 soursop populations, distributed along the geographical range of natural distribution in Java. Genetic diversity wasestimated by RAPD technique using 6 arbitrary selected primers. Those primers produced 151 polymorphic bands with the percentageof polymorphism for each primer ranged from 95% to 100%. The genetic diversity value (h) within each population ranged from 0.0418to 0.0525. The highest h value (0.0525) was found in the KRA population whereas the lowest h value was observed in the PCTpopulation. The highest genetic distance value (0.0410) was observed in SKH-GKD populations pair whereas the lowest geneticdistance value (0.02448) was estimated in KRA-PCT populations pair. Based on the dendogram, the seven soursop populations weresegregated into three major clusters. The first cluster consisted of SKH, KRA, PCT, NGW, and KPG populations. The GKD populationwas then grouped into second cluster. In the third cluster, the BGR population was grouped separately and more genetically distant thanthe others. However, the relationship dendrogram showed that the grouping did not always indicate the geographical origins similarity,but possibly showed the genetic similarity.